Perceptions of Cultural Differences Between Scots and Ukrainians: The Perspective of Ukrainian Forced Migrants - Oksana Oliinyk; Anna Oliinyk (Соціологічні студії)
This article explores the cultural and social differences between Ukrainian forced migrants and their Scottish hosts under the Homes for Ukraine scheme. By employing a qualitative methodology and drawing on interviews with both groups, we analyse the complex relationships that developed during this homestay experience. Despite the initial focus on the practical aspects of hosting, the participants frequently raised issues related to cultural differences. These included diverging perceptions of work-life balance, parenting practices, personal boundaries, and communication styles. Both guests and hosts noted the diligence and cleanliness of Ukrainians. Ukrainian participants also pointed to different attitudes to food as a value, creativity and at the same time, conservatism of the Scots. In turn, the hosts pointed out the blurred personal boundaries of the guests, a more straightforward manner of communication. However, many of them sought cultural exchange in the current situation. However, such experiences were not always positive – a couple of hosts mentioned cases of racism, xenophobia or ageism in the behaviour and statements of their Ukrainian guests, as well as the increased interest of women in men compared to the local population. The findings reveal how these cultural distinctions shaped interactions and created both challenges and opportunities for fostering deeper connections, ranging from formal hospitality to strong friendships and family-like relationships.